Measurement of total normal length of helical cylindrical gears by three-axis indicator on five-axis CNC machine - A. G. Kondrashov; D. T. Safarov (Омский научный вестник)
The article discusses a method for automated measurement of the length of the general normal of a helical cylindrical wheel, which allows to obtain its exact value without removing the part after gear processing with disk or end mills. The measurements are carried out by means of an automated supply of a three-coordinate linear measurement indicator to the calculated measurement points. The formulas for calculating the length of the general normal are given, which allow calculating the value of the length of the general normal and the correction value of the CNC gear ring processing program for two and one-point measurement schemes with the indicator. The use of the two-point method of measuring the length of the general normal with a three-coordinate indicator made it possible to measure the length of the general normal without removing the processed gear wheel from the mandrel, the single-point method completely eliminates the possibility of adjustment defects and reduces the complexity of carrying out machine changeovers in the mode of single and small-scale processing of gears. Comparison of gear measurement data with the three-coordinate indicator Mahr and a specialized CNC gear measuring machine give similar values and confirm the possibility of using the developed scheme to measure the length of the common normal.